The Influence of Community Support on the Sustainability of MSMEs in the Digital Era - Metris, Diksi; Kraugusteeliana, Kraugusteeliana; Amory, Jeffriansyah Dwi Sahputra; Mustafa, Fahrina; Risdwiyanto, Andriya (PT. LITERASI SAINS NUSANTARA, 2024)
With the advancement of technology and internet penetration, the Micro, Small, and Medium Enterprises (MSMEs) sector has undergone significant changes. The digital era presents new opportunities and challenges for MSMEs, enabling them to leverage technology to enhance productivity, marketing, and market access. This research aims to contribute additional insights to the existing literature, focusing on the sustainability of MSMEs amidst the dynamics of the digital era. The study adopts a qualitative approach with an emphasis on literature review, drawing data from Google Scholar during the period 2009 to 2023. The findings indicate that community support plays a crucial role in maintaining the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Awareness of the importance of local products, financial support through investment and crowdfunding, and social support in the form of promotion and active participation form a strong foundation for MSME growth. The strong bond between MSMEs and the community creates an environment in which MSMEs can develop and compete effectively in the dynamic digital market.